2005
DOI: 10.1136/jnnp.2005.065821
|View full text |Cite
|
Sign up to set email alerts
|

Do stroke patients with normal carotid arteries require TEE for exclusion of relevant aortic plaques?

Abstract: Objectives: This study investigated (a) the hypothesis that stroke patients with aortic atheroma would show comparable atherosclerotic changes in the carotid arteries, which are easily accessible for ultrasound evaluation and (b) the possibility of carotid duplex sonography as a replacement for transoesophageal echocardiography (TEE) for the exclusion or prediction of relevant aortic plaques. Methods: In 301 consecutive patients (mean age 62 years) with acute cerebral ischaemia, two dimensional ultrasound meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
3
16
1
Order By: Relevance
“…The predictive value of IMT found in this study is slightly lower than in our previous study, 6 which might have been attributable to the fact that we performed TEE only in those patients without clarified stroke etiology after routine diagnostic testing; ie, patients with Ն80% stenosis of the internal carotid artery or atrial fibrillation were not included. Therefore, a certain number of patients with progressive atherosclerosis of the carotid arteries and the aorta are not represented.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The predictive value of IMT found in this study is slightly lower than in our previous study, 6 which might have been attributable to the fact that we performed TEE only in those patients without clarified stroke etiology after routine diagnostic testing; ie, patients with Ն80% stenosis of the internal carotid artery or atrial fibrillation were not included. Therefore, a certain number of patients with progressive atherosclerosis of the carotid arteries and the aorta are not represented.…”
Section: Discussioncontrasting
confidence: 84%
“…In a previous study, we demonstrated that a normal carotid IMT excluded aortic high-risk sources of cerebral embolism, such as thrombi or plaques Ն4 mm, thus making transesophageal echocardiography (TEE) dispensable for assessment of the aorta. 6 However, in concordance with others, 7 positive predictive values were low.…”
supporting
confidence: 83%
“…This result is in accordance with the findings of Harloff et al [25] in which CIMT ≤0.9 mm had a 95.8% negative predictive value for aorta plaques >4 mm thick. The positive predictive value of CIMT >0.9 mm was only 29.6% but increased to 33% in the presence of plaque in the carotid artery.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings are consistent with recent studies suggesting the use of CIMT testing for the exclusion of significant aortic atheroma. 8,9,17 In a prospective study, Harloff et al reported that use of CIMT testing achieved a negative predictive value of 92% for the detection of complex aortic atheroma. 9 Complex aortic plaques are particularly important to exclude because they are associated with a increased risk of recurrent stroke and may warrant therapy with statins or warfarin.…”
Section: Discussionmentioning
confidence: 99%